2012
DOI: 10.1121/1.4734241
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to a break in interaural correlation is co-modulated by intensity level and interaural delay

Abstract: This study investigated whether sound intensity affects listeners' sensitivity to a break in interaural correlation (BIC) embedded in wideband noise at different interaural delays. The results show that the detection duration threshold remained stable at the intensity between 60 and 70 dB SPL, but increased in accelerating fashion as the intensity decreased toward 40 dB SPL. Moreover, the threshold elevated linearly as the interaural delay increased from 0 to 4 ms, and the elevation slope became larger as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…This and previous studies [23], [24], [40][42] have shown that the longest IAI for detecting the BIC is far beyond the longest physiological interaural delay that is due to the difference in the direct propagation paths to the two ears for a source in the space, implying the possibility that PAM occurs at the central level [41]. Moreover, the results of this study indicate that the temporal extent of PAM (measured at the longest IAI for detecting the BIC) is even longer than the temporal threshold for binaural fusion (i.e., the longest IAI for maintaining the perceptual fusion of the interaurally correlated noises).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This and previous studies [23], [24], [40][42] have shown that the longest IAI for detecting the BIC is far beyond the longest physiological interaural delay that is due to the difference in the direct propagation paths to the two ears for a source in the space, implying the possibility that PAM occurs at the central level [41]. Moreover, the results of this study indicate that the temporal extent of PAM (measured at the longest IAI for detecting the BIC) is even longer than the temporal threshold for binaural fusion (i.e., the longest IAI for maintaining the perceptual fusion of the interaurally correlated noises).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, introducing a change in interaural correlation of the arbitrary noises does not alter the energy and spectrum but modifies some perceptual dimensions such as the compactness, number of images, and lateral position. Consequently, human listeners with normal hearing are able to detect a dynamic break in interaural correlation (BIC) (i.e., a brief drop of interaural correlation from 1 to 0 and then return to 1, Figure 1A) in interaurally correlated steady-state noises [23], [24], [35], [36], [40][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the delay increases to a certain value, it becomes difficult for listeners to discriminate the sound image(s) resulted from the fusion of physically correlated lead and lag from the sound image(s) resulted from the fusion of physically uncorrelated lead and lag. Therefore, one way to quantify the strength of the lead-lag fusion at a certain delay is to measure the detection of a change in the correlation between the lead and lag from 1 to 0 and then returning back to 1 [7, 8, 11, 13, 14]. This change in the correlation has been termed break in correlation (BIC) in previous studies [1517].…”
Section: Introductionmentioning
confidence: 99%
“…Although the psychoacoustics associated with this lead-lag fusion have been well documented [7, 8, 11, 13, 14], its underlying neural mechanisms in human listeners are poorly understood. Our previous study [18] has shown that the BIC can evoke a scalp potential consisting of an N1 and a P2 component and that the absolute difference in the peak amplitude of these two components (i.e., the N1-P2 peak-to-peak amplitude) decreases with an increase of the delay.…”
Section: Introductionmentioning
confidence: 99%